Gunshot wound with transfixation of both hemithorax and transmediastinal tract - Asiner, Boris (Cirugía del Uruguay, 1972)
A ,62-year-old patient with transfixing wound in both hemithoraces caused by a bullet which followed " high and posterior transmediastinal path, entered the hospital after a 20-hour evolution, suffering from shock. There was subcutaneous emphysema. During revival practices the emphysema extended considerably, the patient's condition became worse and exploratory thoracotomy was indicated. In view of the clinical characteristics of the wound and the path followed by the bullet, the approach chosen was through high right side thoracotomy. On the right side there was an important hemopneumothorax and, through a mediastinal gap, a slight one on the left side. There was considerable insuflation of the mediastine under _ tension, which was inmediately corrected by an opening incision which practically depleted the pneumomediastine. This right side approach made it possible not only. to sol ve the serious condition of the left wounds, simple closure and control drainage in the fore part of the thorax, third space, but also to attend to the lesions on he righ side, their suture and drainage. Postoperatory evolution was eventless and the patient was discharged on the 8th. day. We believe that the lesion on the mediastinal effraction were the main causes of the considerable mediastinal insuflation and extensive emphysema.